Development of Arduino Uno-Based Automatic Control and Monitoring Prototype for Fire Pump System in Local Industrial Community - Wahyu Eko Prasetiyo; Annas Singgih Setiyoko (Politeknik Perkapalan Negeri Surabaya, 2024)
Advancements in science and technology have significantly integrated electronic systems into various fields. Many industrial tools that previously relied on manual labor have been replaced by machines operating with electrical circuit intelligence. In response to this trend, the authors developed an automatic control switch for fire pumps. This device aims to simplify the operation of switching between two pumps, transforming the process from manual to automatic. Additionally, the system can activate both pumps upon detecting smoke, indicating a fire incident. Beyond improving time efficiency and reducing human error, this tool also monitors the current and voltage directed to the pumps, functioning as a datalogger to record monitoring results. These recorded data, including timestamps, allow technicians to evaluate and address potential damages during maintenance effectively. The busy nature of industrial work highlights the benefits of tools designed to assist workers and prevent disruptions in their tasks. Therefore, enhancing time efficiency requires the development of tools that streamline various processes. To ensure the proposed device meets industry needs and operates smoothly, the authors conducted observations in industrial settings and engaged in discussions with workers to gather relevant data. This data collection process, which also utilized web-based searches, was essential for identifying features to incorporate into the device. After identifying the problems, the concept and design of the tool were developed under the supervision of On-the-Job Training (OJT) mentors. The result was a comprehensive tool designed to ease the workload of industrial workers. The inclusion of a datalogger in this device addresses a critical need in industries for conducting regular maintenance. The system's ability to store data facilitates periodic evaluations and improves the overall efficiency of maintenance activities.